Consequences of a Smoker's Husband in the Dimension of Household Harmony Perspective of Islamic Law - Nurchaliq Chaliq Majid; Anna Rahma Syam; Suharna Arna Ismail (Al-Adalah: Jurnal Hukum dan Politik Islam, 2023)
Smoking habit can also affect the harmony of a family. This paper presents how Islam views the consequences of a smoking husband to the marital harmony. This qualitative research was performed using Phenomenological and No rmative Descriptive approach. The Phenomenological approach allowed for the discovery of facts about social phenomena in society, while the Normative Descriptive approach resulted in legal conclusions regarding the phenomena identified using the previous approach. In this research, wives who participated as samples did not found their marital harmony significantly affected by the cigarette smoke and they were not bothered to end the marriage due to it. Seen from another perspective, only fate can end a marriage, not cigarette smoke. In the context of Islamic Law, while some scholars may permit it, the majority of scholars prohibit smoking based on several verses in the Qur'an